Consumer Attitudes toward Consumption of Meat Products Containing Offal and Offal Extracts - Mar Llauger; Anna Claret; Ricard Bou; Laura López-Mas; Luis Guerrero (Foods, 2021)
The development of food products containing offal and offal extracts could be part of the solution to the upcoming demand for animal protein. This study aimed to determine Spanish consumers’ attitudes toward offal and the development of meat products containing offal extracts. Consumers’ perceptions were evaluated by means of focus group discussions and a survey (N = 400) to validate the focus group results in various Spanish provinces. The theory of planned behavior was used to examine consumer attitudes. Results indicated that nutritional properties, environmental sustainability, and affordability were the main drivers, while sensory attributes, low frequency consumption, and perceived higher content of undesirable compounds were the main barriers. Three segments were identified according to their beliefs: those in favor of these products, those that were health and environmentally conscious, and those who were reluctant about them. The identification of these segments and their profiles demonstrated the necessity to focus efforts on providing reliable information on sensory and health-related issues to improve acceptability. Attitude was the most important predictor of behavioral intention regarding the global model, while the social component (subjective norm) was significant for two of the identified segments, emphasizing the relevance of the social component for acceptability.